Adverse birth outcomes among native-born and foreign-born mothers in Taiwan: A population-based birth cohort study - Shiao Laura; Chiang Tung-liang (BMC, 2012)
Abstract Background The number of children born to foreign-born mothers in Taiwan has significantly increased since the 1990s. These foreign-born mothers are mainly from China and Southeast Asia. Children born to foreign-born mothers, according to media reports, are subject to inferior health. This study sought to determine whether socioeconomic disparities in birth outcomes exist between native and foreign-born mothers in Taiwan. Methods Analysis data were obtained from the Taiwan Birth Cohort Study of 20,090 nationally representative 6-month-old babies, born in 2005. The data on the babies were divided into two groups, those of foreign-born mothers and those of Taiwanese mothers. The health outcome variables that were examined included two adverse birth outcomes: low birth weight and preterm birth. Multiple logistic regression was used to examine the association between income and foreign-born status, as well as birth outcomes among both groups. Results Children of native Taiwanese mothers had a higher prevalence of low birth weight (6.9%) than did children of China-born (4.7%) and Southeast Asia-born mothers (5.2%). The prevalence of preterm birth was also higher among children of native Taiwanese mothers (8.4%) than among children of Southeast Asia-born (7.2%) and China-born mothers (6.3%). Foreign-born status was associated with lower odds of low birth weight among families with a monthly family income < NT$30,000 (adjusted odds ratio (AOR) = 0.24, 95% confidence interval (CI) = 0.14-0.42, p < 0.001), and lower odds of preterm birth among families with a monthly family income < NT$30,000 and NT$30,000-69,999 (AOR = 0.63, CI = 0.40-0.99, p < 0.05, and AOR = 0.68, CI = 0.53-0.88, p < 0.01, respectively). Having a higher monthly family income (NT$70,000+ and NT$30,000-69,999) was associated with lower odds of low birth weight (AOR = 0.59, CI = 0.46-0.77, p < 0.001 and AOR = 0.75, CI = 0.60-0.94, p < 0.05, respectively) among Taiwanese mothers, but not among foreign-born mothers. Conclusion Foreign-born mothers from China and Southeast Asia did not experience worse birth outcomes than native Taiwanese mothers did, regardless of the disadvantaged socioeconomic position of their families.